2017
DOI: 10.1016/j.bbamem.2016.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Mapping out the intricate relationship of the HIV envelope protein and the membrane environment

Abstract: The HIV gp160 envelope fusion protein is situated in the viral membrane and mediates virus entry into its host cell. Increasing evidence suggests that virtually all parts of the HIV envelope are structurally and functionally dependent on membranes. Protein-lipid interactions and membrane properties influence the dynamics of a manifold of gp160 biological activities such as membrane fusion, immune suppression and gp160 incorporation into virions during HIV budding and assembly. In the following we will summariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 212 publications
1
14
0
Order By: Relevance
“…Significant leakage of contents and lipid mixing was observed upon VL LUV incubation with MPER(671À693) or MPER(671À693)L679I peptides. Interestingly, the TMD(684À704) peptide also induced lipid mixing, an observation consistent with data previously reported in the literature (see for a recent review (48)). Thus, VL vesicle destabilization correlated with the observed virucidal effects of the peptides MPER(671À693) or MPER(671À693)L679I.…”
Section: Resultssupporting
confidence: 91%
“…Significant leakage of contents and lipid mixing was observed upon VL LUV incubation with MPER(671À693) or MPER(671À693)L679I peptides. Interestingly, the TMD(684À704) peptide also induced lipid mixing, an observation consistent with data previously reported in the literature (see for a recent review (48)). Thus, VL vesicle destabilization correlated with the observed virucidal effects of the peptides MPER(671À693) or MPER(671À693)L679I.…”
Section: Resultssupporting
confidence: 91%
“…Conformational transition of fusion protein often exposes buried hydrophobic fusion peptide from the core structure. Fusion peptide inserts into the outer leaflet of the plasma membrane of the host cell initiating membrane fusion process [5][6][7][8][9]. Understating fusion mechanism not only garners knowledge of virus pathology but also can be exploited for the development of antiviral drugs [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The Env protein complex of HIV is of utmost biomedical importance because it mediates the contact of the virus with the target cell and assures the fusion of the viral and cellular membranes. Therefore, gp41 or gp120, the building blocks of Env, are prime targets to interfere with the infections cycle of the virus [10,53,54]. Furthermore, a number of broadly neutralizing antibodies have been identified that target conserved regions of the protein complex [55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…The following fusion events are then driven by gp41 membrane interactions [10], a protein which has received particular attention also in this work (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation